Urea nitrogenated mesoporous activated carbon derived from oil palm empty fruit bunch for high-performance supercapacitor. (1st August 2022) - Rustamaji, Heri; Prakoso, Tirto; Devianto, Hary; Widiatmoko, Pramujo; Saputera, Wibawa Hendra
Abstract: This study aims to synthesize urea nitrogenated activated carbon (N-ACU) derived from oil palm empty fruit bunches and examine its performance as a supercapacitor electrode. The synthesis was carried out in three stages: hydrothermal carbonization with CaCl2 activator, impregnation with urea, and activation of nitrogenated hydrochar with CO2 gas. The urea to hydrochar impregnation ratio was varied by weight at 1, 2, and 3, while physical characterization of the material was carried out by SEM, XRD, adsorption/desorption isotherms, and FTIR. Porosity analysis showed that all the samples had a mesoporous structure with 3.3–5.8 nm and a BET surface area of 363.88–640.61 m 2 g −1 . Furthermore, the electrochemical characterization indicated that the optimum result was obtained for the N-ACU3 sample with an electrode-specific capacitance value of 176.76 F g −1 at a scan rate of 2 mV s −1 . The highest energy and power density values at the current of 1 A g −1 were 19.89 Wh kg −1 and 1431.20 W kg −1, respectively. Durability tests of supercapacitor carried out by cyclic charge-discharge for 5000 cycles showed that the coulombic efficiency and capacitance retentions were approximately 100% and 98.7%, respectively. Based on the results, the urea to hydrochar impregnation ratio affects the characteristic of N-ACU and the performance of supercapacitors. In addition, urea nitrogenated treatment on activated carbon can reduce the ohmic and charge transfer resistance and maintain the supercapacitor's cell stability. The improved supercapacitor performance indicates that the Synthesis of nitrogenated activated carbon from biomass waste can be a promising method for producing electrode materials. Highlights: The nitrogenated mesoporous activated carbon (N-ACU) was successfully produced from empty fruit bunches of oil palm. The urea to hydrochar impregnation ratio affects the characteristic of N-ACU and the performance of supercapacitors N-ACU carbon has a pore size from 3.3-5.8 nm and a specific surface area of 445.18-640.61 m 2 g -1 . The optimum specific capacitance, energy, and power density values were 176.76 F g -1, 19.89 Wh kg -1, and 1431.20 W kg -1 . Coulombic efficiency and capacitance retention for N-ACU-based supercapacitors were 100% and 98.7%, respectively.